2016
DOI: 10.3390/rs8120972
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Winter Wheat Biomass and Yield by Combining the AquaCrop Model and Field Hyperspectral Data

Abstract: Knowledge of spatial and temporal variations in crop growth is important for crop management and stable crop production for the food security of a country. A combination of crop growth models and remote sensing data is a useful method for monitoring crop growth status and estimating crop yield. The objective of this study was to use spectral-based biomass values generated from spectral indices to calibrate the AquaCrop model using the particle swarm optimization (PSO) algorithm to improve biomass and yield est… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
43
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 88 publications
(43 citation statements)
references
References 53 publications
0
43
0
Order By: Relevance
“…These dry matter indices expectedly performed better than the chlorophyll indices for the estimation of total biomass. A recent study by Jin et al [18] showed the better performance of the NDMI for biomass estimation than a few chlorophyll indices, but did not consider the ND LMA . Gnyp et al [27] determined (R 1301 − R 1706 )/(R 1301 + R 1706 ), of which the two bands were approximately 20 nm offset from their counterparts in the ND LMA , as their best wavelength combination for the estimation of the total biomass in rice.…”
Section: Why Did Dry Matter Indices Work Better Than Chlorophyll Indimentioning
confidence: 99%
“…These dry matter indices expectedly performed better than the chlorophyll indices for the estimation of total biomass. A recent study by Jin et al [18] showed the better performance of the NDMI for biomass estimation than a few chlorophyll indices, but did not consider the ND LMA . Gnyp et al [27] determined (R 1301 − R 1706 )/(R 1301 + R 1706 ), of which the two bands were approximately 20 nm offset from their counterparts in the ND LMA , as their best wavelength combination for the estimation of the total biomass in rice.…”
Section: Why Did Dry Matter Indices Work Better Than Chlorophyll Indimentioning
confidence: 99%
“…These models to estimate the AGB use the original VIs and are validated by using VIs with noise added. In these tests, the signal-to-noise ratio (SNR) is set to 5,10,15,20,30, and 50 (the noise increases with decreasing SNR). We also compare the results to those obtained with noiseless VIs.…”
Section: Noise Simulationmentioning
confidence: 99%
“…One such variable, above-ground biomass (AGB), plays an important role in plant functioning because it reflects the status of crop growth and is related to solar-energy consumption, yield, and grain quality [3,4]. Therefore, AGB is considered as one of the most important crop biophysical parameters, and its accurate estimation can help improve crop monitoring and yield prediction [5]. Traditional AGB estimates are based on destructive measurements, which are not only time and labor consuming, but more importantly, are difficult to apply over large areas [6].…”
Section: Introductionmentioning
confidence: 99%
“…In their work, Jin et al [112] used FAOs' AquaCrop model and calibrated using spectral-based biomass values generated from fifteen spectral indices and particle swarm optimization (PSO). The primary goal of their work was to improve yield and biomass prediction of winter wheat yield in China, by assimilating field spectroscopic data into AquaCrop model with PSO algorithm.…”
Section: Limitations and Advantages Of Using Remote Sensing Data Withmentioning
confidence: 99%